IMPLEMENTATION OF THE CONCEPT OF FAMILY ENVIRONMENTAL EDUCATION FROM A HADITH PERSPECTIVE - Mukti, Abdul; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2023)
The family is a living unit that provides a child's learning situation. The main task of the family for children's education is to lay the foundation for education. This means that families must also understand problems or matters related to how to educate children according to child development. The family's contribution to children's education is that children are trained to master how to take care of themselves, for example eating, talking, walking, praying. This is closely related to the child's personal development. This research method is literature, namely collecting important data or documents and looking at the nature of the research analyzed through qualitative research which is a descriptive research. ;1. Prioritizing religious and moral education for children. 2. Fulfillment of family income. Automatically Islamic education will become 5 parts 1) High moral formation due to Islamic education, without neglecting physical education, reason and practical knowledge; 2) Preparing and equipping children to look at life in this world and in the hereafter; 3) Grow and develop all aspects that can provide benefits; 4) Providing and cultivating scientific tips and enthusiasm by studying various sciences for the sake of science itself; and 5) Providing provision of professional skills for survival as capital for making a living